TSH-CHECK-1 Test: Diagnostic Accuracy and Potential Application to Initiating Treatment for Hypothyroidism in Patients on Anti-Tuberculosis Drugs - Kosack, Cara S.; Page, Anne-Laure; Van Hulsteijn, Leonie T.; Lentjes, Eef G. W. M. (PloS one, 2012)
Thyroid-stimulating hormone (TSH) promotes expression of thyroid hormones which are essential for metabolism, growth, and development. Second-line drugs to treat tuberculosis (TB) can cause hypothyroidism by suppressing thyroid hormone synthesis. Therefore, TSH levels are routinely measured in TB patients receiving second-line drugs, and thyroxin treatment is initiated where indicated. However, standard TSH tests are technically demanding for many low-resource settings where TB is prevalent; a simple and inexpensive test is urgently needed. As a proof of concept study TSH was measured in routinely collected sera at the University Medical Center Utrecht, Netherlands, using the TSH-CHECK-1 (VEDALAB, Alençon, France), a lateral-flow rapid immunochromatographic assay with a TSH cut-off value of 10 µIU/mL, the standard threshold for initiating treatment. These results were compared with TSH levels measured by a reference standard (UniCel DXi 800 imunoassay system, Beckman Coulter, USA). Sensitivity, specificity, and likelihood ratios were then calculated. A total of 215 serum samples were evaluated: 107 with TSH values <10 µIU/mL and 108 with values ≥10 µIU/mL. TSH-CHECK-1 test sensitivity was found to be 100.0% (95% CI: 96.6-100.0) and specificity was 76.6% (95% CI: 67.5-84.3). Predictive values (PV) were modelled for different levels of prevalence. For a prevalence of 10% and 50%, the positive PV was 32.2% (95% CI: 25.0-39.7%) and 81.1% (95% CI: 75.0-85.5%), respectively; the negative PV was 100% (95% CI: 98.9-100%) and 100% (95% CI: 91.3-100%) respectively. The TSH-CHECK-1 rapid test was practical and simple to perform but difficult to interpret on weak positive results. All sera with TSH≥10 µIU/mL were correctly identified, but the test lacked sufficient specificity. Given its excellent negative PV in this evaluation, the test shows promise for ruling out hypothyroidism. However, so far it appears that samples testing positive with TSH-CHECK-1 would require confirmation using another method.